2020
DOI: 10.3390/genes11030278
|View full text |Cite
|
Sign up to set email alerts
|

Seascape Genetics and the Spatial Ecology of Juvenile Green Turtles

Abstract: Understanding how ocean currents impact the distribution and connectivity of marine species, provides vital information for the effective conservation management of migratory marine animals. Here, we used a combination of molecular genetics and ocean drift simulations to investigate the spatial ecology of juvenile green turtle (Chelonia mydas) developmental habitats, and assess the role of ocean currents in driving the dispersal of green turtle hatchlings. We analyzed mitochondrial (mt)DNA sequenced from 358 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Even for mobile species, able to swim actively while performing migrations or ontogenetic shifts in habitat use (Abecasis et al, 2009;Almpanidou et al, 2019), PD alone can explain more than 50% of the variation in genetic dispersal estimates (Kinlan and Gaines, 2003). Taxa without planktonic dispersal stages might also benefit from some aid in transportation by oceanographic currents, as suggested for some taxa like green turtles (e.g., Jensen et al, 2020), but not others (e.g., Briscoe et al, 2016).…”
Section: Mpa Aggregationsmentioning
confidence: 99%
“…Even for mobile species, able to swim actively while performing migrations or ontogenetic shifts in habitat use (Abecasis et al, 2009;Almpanidou et al, 2019), PD alone can explain more than 50% of the variation in genetic dispersal estimates (Kinlan and Gaines, 2003). Taxa without planktonic dispersal stages might also benefit from some aid in transportation by oceanographic currents, as suggested for some taxa like green turtles (e.g., Jensen et al, 2020), but not others (e.g., Briscoe et al, 2016).…”
Section: Mpa Aggregationsmentioning
confidence: 99%
“…Although migratory data of juvenile green turtles are limited (e.g. Sanchez et al 2020), oceanic currents play an important role in the distribution of juvenile green turtles through the WIO (Jensen et al 2020). Four satellite tags deployed on juvenile green turtles in southern Tanzania showed that they stayed close (approximately 10 km) to the capture site (Sea Sense 2017).…”
Section: Green Turtlementioning
confidence: 99%
“…Although research on the genetic structure of coastal populations of green, hawksbill, and loggerhead turtles has been conducted (Bourjea et al 2015b, Fernandes 2015, Anastácio & Pereira 2017, Jensen et al 2020, the experts noted that further work is needed to place the coastal foraging and nesting populations of all 5 species in a regional context (Fig. 4B).…”
Section: Genetic Connectivitymentioning
confidence: 99%
“…Recent studies that integrated phylogeographic inference, numerical ocean circulation models, and Lagrangian simulation of individual particle trajectories (van Sebille et al ., 2018) have greatly improved our knowledge of the ecological factors driving evolution in the oceans. These include studies of genetic structure (Bertola et al ., 2020; Sefc et al ., 2020), connectivity and establishment (Jensen et al ., 2020; Nikolic et al ., 2020) of marine organisms. For terrestrial plants, mechanistic dispersal simulations also have been used to predict propagule transoceanic dispersal of mangroves (Van der Stocken et al ., 2019), seagrasses (Smith et al ., 2018) and Urticaceae (Wu et al ., 2018), and to confirm the origin of pre‐Columbian bottle gourds (Kistler et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%